"Hopefully I Can Transfer:" Cooling Out Postsecondary Aspirations of Latina/o/x Students. Issue 4 (1st October 2020) - Acevedo, Nancy
ABSTRACT: Guided by the frameworks of college- conocimiento and the cooling out function, this study examined the college choice process of Latina/o/x students who attended an under-resourced urban high school. Data for this study consisted of interviews with ten institutional agents, two oral history interviews with 34 Latina/o/x students, and observation field notes. Findings revealed that upon seeking college information, students were informed that the community college was more accessible than four-year college. The consistent message from advisors and teachers influenced the participants to enroll in community college, with aspirations to transfer to a four-year college. Upon applying to college, recruitment counselors from for-profit and community colleges offered vocational pathways as an alternative option to transferring. Implications for equity-minded research are discussed. Recommendations for socially just policies and asset-based practices are provided to bridge the high school-to-ollege transition for Latina/o/x students.